Patient Dosimetry Assessment During Lateral Cervical and Lumbar Spine Radiography in Selected Hospitals and Clinics in Al-Najaf, Iraq - Haider N. Kanbar; Hussien A. Ali Mraity; Amar H. Mahdi (Iraqi Journal of Physics, 2026)
Radiographic examinations of the cervical and lumbar spine are common diagnostic tests that can involve relatively high radiation exposure for the patient, particularly in lateral projections. The objective of this study was to evaluate the Entrance Surface Dose (ESD) in adult patients during lateral radiographic imaging of the cervical and lumbar spine and to benchmark the findings against internationally published data. A prospective survey was conducted in six radiographic facilities, comprising three governmental hospitals and three private clinics. A total of 221 adult patients were included, comprising 107 cervical spine LAT examinations and 114 lumbar spine LAT examinations. The exposure parameters, tube potential (kVp), tube current (mAs), and source-image-distance (SID), as well as patient data, were recorded. The ESD was estimated using the Edmonds dosimetric model and assuming a backscatter factor of 1.35. Mean ESD values ranged from 0.26 to 0.80 mGy for cervical spine LAT examinations and from 1.45 to 4.30 mGy for lumbar spine LAT examinations, with overall mean values of 0.52 mGy and 3.48 mGy, respectively. Lumbar spine examinations consistently yielded higher ESD values than the cervical spine examinations due to the greater anatomical thickness and X-ray attenuation. Furthermore, ESD values were significantly higher for lumbar spine LAT examinations performed in private clinics than in governmental hospitals (p < 0.001). The obtained ESD values were generally within internationally reported ranges. These results highlight the need for standardized protocols, quality control, and local diagnostic reference levels (LDRLs) for providing optimal patient protection.